APLIKASI PENGELOLAAN DATA PENGANGGARAN PENGADAAN BARANG DI PT. DHIMAS MITRA INTERNASIONAL MENGGUNAKAN BAHASA PEMROGRAMAN MOBILE - Taufik hidayat taufik (LPPM Institut Citra Buana Indonesia, 2026)
The budgeting process for goods procurement at PT. Dhimas Mitra Internasional is currently still carried out conventionally, which often results in delays in data synchronization and budget validation. This study aims to develop a mobile application that can manage budgeting data in an integrated and real-time manner. The research methods used include observation, interviews, and system development using the Waterfall model. The system is designed with UML diagrams and implemented using mobile programming languages. The research results show that this application is able to accelerate the process from submission to approval of goods procurement budgets. With the mobile-based system, management can carry out monitoring and decision-making more efficiently without being bound by space and time.